Implementation of EM Algorithm in Data Mining for Clustering Female Cooperative - Widya, Putu Angelina; Sudarma, Made (International Journal of Engineering and Emerging Technology; Vol 3 No 1 (2018): January - June, 2018)
Cooperatives have a key role for women by providing access to generating income activities. Women have access to general production resources like credit, land, marketing facilities, infrastructure, equipment, and technology. All of that resources can increase their income. By shaping themselves into cooperatives, they can get benefit from economies scale and increase their access to the labor market. Cooperatives can be the best instruments to improve women’s welfare and for the development of transformations such as more open minded by using the most profitable female cooperatives. As one of the existing regencies in Bali Province, Gianyar regency has rapid development of female cooperative. In this research will clustering female cooperative by using WEKA application with Expectation-Maximization Algorithm. From the result, government can maintance which female cooperation should be put on watchlist.